Marriage and Family Experience of Northeast India - KALITA, DR JYOTI PRASAD (The journal of contemporary issues in business and government, 2021)
Man is a gregarious animal; in other words man lives in social groupings. Understanding man and society implies appreciating and understanding the very nature of man and the structural organization of human society. This very nature of man not wanting to live in isolation but instead in association with fellow humans necessitated the need for man to create the institutions of the family and marriage, through which every individual in the social group develops an identity and a distinctive origin. Being one of the matriarchal tribes of the world here the woman’s side offers the marriage and the houses bear the name of a woman instead of a man and they consider their descent through the female line. Though they have their age old cultural beliefs and practices for marriage, due to some external factors there seem to be a transition in their marriage system.